Association between clinical features and course of systemic sclerosis and serum interleukin-8, vascular endothelial growth factor, basic fibroblast growth factor, and interferon alpha - Joanna Kosałka-Węgiel; Sabina Lichołai; Sylwia Dziedzina; Mamert Milewski; Piotr Kuszmiersz; Anna Korona; Mariusz Korkosz; Jolanta Gąsior; Aleksandra Matyja-Bednarczyk; Helena Kwiatkowska; Andżelika Siwiec-Koźlik; Wojciech Sydor; et al. (Advances in Clinical and Experimental Medicine, 2024)
Certain mediators, such as soluble growth factors and cytokines, among others, are implicated in the immunopathogenesis of systemic sclerosis (SSc). This study aimed to examine the association between serum levels of vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), interferon alpha (IFN-α), and basic fibroblast growth factor (bFGF) and the clinical presentation and course of SSc. This longitudinal, observational study included 43 patients with SSc and 24 healthy subjects. Serum concentrations of VEGF, IL-8, IFN-α, and bFGF were measured at baseline in patients previously treated for SSc. Medical history of patients was analyzed retrospectively at the time of cytokine measurement to infer clinical correlations, and during follow-up for a median of 5 years, assessing the incidence of death or cancer. The bFGF and IFN-α concentrations differed between SSc patients and controls (p < 0.01). In turn, organ involvement and SSc phenotypes did not impact studied cytokine concentrations, similar to systemic steroid and/or immunosuppressant use at enrollment. However, we have documented a positive correlation between the current oral steroid dose and serum levels of IL-8 and bFGF. Furthermore, patients with a VEGF level ≥95.7 pg/mL and IFN-α level ≥3.6 pg/mL required cyclophosphamide therapy more often, currently or in the past (approx. 3-fold and 4-fold, respectively). Substantially elevated VEGF and IFN-α concentrations at baseline were associated with higher cancer occurrence (n = 4) during follow-up, while elevated circulating IL-8 level was associated with an increased risk of death (n = 9). The SSc group was characterized by higher serum concentrations of bFGF and IFN-α compared to healthy controls. Patients treated with cyclophosphamide or receiving higher systemic steroid doses, thus suffering from a more severe disease type, had increased cytokine levels. Elevated circulating IFN-α and VEGF levels might be correlated with cancer, whereas raised IL-8 levels may be associated with an increased risk of death. However, further research is needed to verify our findings.